Development of nanoengineered thulium-doped fiber laser with low threshold pump power and tunable operating wavelength - Paul, M.C.; Dhar, A.; Das, S.; Latiff, A.A.; Ahmad, M.T.; Harun, Sulaiman Wadi (Institute of Electrical and Electronics Engineers (IEEE), 2015)
A tunable and low-threshold thulium (Tm)-doped fiber (TDF) laser is demonstrated using a new silica-based nanoengineered TDF in a linear configuration, in conjunction with 1552-nm pumping. The TDF used in these experiments had a Tm-doped nanoengineering yttrium-alumina-silica glass core with a diameter of 13.43 mu m and 0. 21 NA, which is surrounded by a pure silica inner cladding with normal acrylate polymer resin coating. The nanoengineered TDF was fabricated using a modified chemical vapor deposition (MCVD) process, in conjunction with a solution-doping technique. The fabricated fiber shows an absorption loss of 165 dB/m at 793 nm. A maximum lasing slope efficiency of 26.2 was obtained at a 1910-nm wavelength using the fabricated fiber with an optimum length of 5 m. The maximum output power of 138 mW was achieved at the maximum pump power of 1100 mW. The lowest pump power threshold of 693 mW for a 1552-nm wavelength was obtained at a TDF length of 7 m. The operating wavelength of the laser could be continuously tuned from 1890 to 1910 nm with an optical signal-to-noise ratio better than 43 dB, whereas the slope efficiency of the laser varies from 16.4 to 19.7.